Differentiation of Human Dermal Mesenchymal Stem Cells into Cardiomyocytes by Treatment with 5-Azacytidine: Concept for Regenerative Therapy in Myocardial Infarction. (28th March 2013) - Potdar, Pravin D.; Prasannan, Preeti
Abstract : Myocardial infarction (MI) is the leading cause of death worldwide. Stem cells regenerative medicine offers a promising approach to cure such degenerative disorders. Mesenchymal stem cells are thought to be one of the important types of stem cells which can differentiate into various lineages such as neuron, hepatocytes, and cardiomyocytes. In the present study, human dermal mesenchymal stem cells (hDMSCs) have been developed from human scalp punch biopsy and characterized for their mesenchymal phenotype so that these cells can be useful for differentiating into cardiomyocytes. 5-Azacytidine induces cardiomyocyte differentiation in vitro and therefore it has been used to differentiate hDMSCs cells into cardiomyocytes. It was observed that hDMSCs differentiated into cardiomyocyte within a period of 4 days to 15 days after treatment with 10 μ M and 20 μ M of 5-azacytidine. The cardiomyocyte phenotype was confirmed by studying expression of α -cardiac actin, β -myosin heavy chain, and cardiac troponin T. Thus, this paper describes the differentiation of hDMSCs into cardiomyocytes which can be further be used for treatment of MI. This type of cell-based cardiac therapy will offer a new hope for millions of patients worldwide who are suffering from heart disease.